2006
DOI: 10.1016/j.micinf.2005.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Isolates of Candida albicans that differ in virulence for mice elicit strain-specific antibody-mediated protective responses

Abstract: Three distinct isolates of Candida albicans were used to establish systemic and oral infections in inbred mice that are genetically resistant or susceptible to tissue damage. Patterns of infection differed significantly between both yeasts and mouse strains. Systemic infection conferred significant protection against re-challenge with the homologous, but not the heterologous yeast; however, the protective effect was more evident in the tissue-susceptible CBA/CaH mice than in the resistant BALB/c strain. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
1
18
0
1
Order By: Relevance
“…Although it has long been accepted that isolates of C. albicans differ in virulence for mice, only recently has it been shown that distinct isolates elicit antibodies that show substantially different patterns of epitope recognition and that differ in their ability to confer protection in vivo 10 . The present study has extended these observations to the cellular arm of the immune system, by showing that both neutrophils and macrophages from tissue‐susceptible and tissue‐resistant mice show quantitative differences in phagocytosis and killing of the three isolates of the yeast.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although it has long been accepted that isolates of C. albicans differ in virulence for mice, only recently has it been shown that distinct isolates elicit antibodies that show substantially different patterns of epitope recognition and that differ in their ability to confer protection in vivo 10 . The present study has extended these observations to the cellular arm of the immune system, by showing that both neutrophils and macrophages from tissue‐susceptible and tissue‐resistant mice show quantitative differences in phagocytosis and killing of the three isolates of the yeast.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the increased severity of tissue damage in CBA/CaH as compared with BALB/c mice. The differences in killing of the various yeast isolates, seen after opsonization with normal serum, may be correlated to various surface properties of the yeasts, such as the ability to bind complement regulatory proteins that can inhibit the binding of opsonins to the cell surface, 19 but as the three yeast isolates elicit distinct antibody profiles after systemic immunization, 10 differences in the killing efficiency after opsonization with immune serum are probably correlated to the specificity of antibodies raised against the individual yeasts. Our study was able only to measure the additive effect of antibody over and above the effect of complement in normal serum and hence the sensitivity of detection of specific antibody‐mediated effects may have been low.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations